2021
DOI: 10.1002/med.21869
|View full text |Cite
|
Sign up to set email alerts
|

Role of membrane proteins in bacterial resistance to antimicrobial peptides

Abstract: Several natural antimicrobial peptides (AMPs), including the novel semisynthetic lipoglycopeptide antibiotics telavancin, dalbavancin, and oritavancin, have been approved for clinical use to address the growing problem of multiple antibioticresistant Gram-positive bacterial infections. Nevertheless, the efficacy of these antibiotics has already been compromised. The SARS-CoV-2 pandemic led to the increased clinical use of all antibiotics, further promoting the development of bacterial resistance. Therefore, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…This clinically isolated strain carried two well-characterized mutations in gyrA (S83L and D87N) causing a high-level fluoroquinolone resistance, as well as a higher-than-normal spontaneous mutation rate [ 19 ]. Approved by WHO as the main drug for the treatment various infections caused by Cram-negative bacteria including multidrug-resistance strains, polymyxin B was taken as the reference agent [ 20 ]. This experiment indicated that abarenicins induced a low-level stable resistance of E. coli with MICs up to 4-fold (for Ap11) and 8-fold (for Ap9) higher than those of the wild-type strain.…”
Section: Resultsmentioning
confidence: 99%
“…This clinically isolated strain carried two well-characterized mutations in gyrA (S83L and D87N) causing a high-level fluoroquinolone resistance, as well as a higher-than-normal spontaneous mutation rate [ 19 ]. Approved by WHO as the main drug for the treatment various infections caused by Cram-negative bacteria including multidrug-resistance strains, polymyxin B was taken as the reference agent [ 20 ]. This experiment indicated that abarenicins induced a low-level stable resistance of E. coli with MICs up to 4-fold (for Ap11) and 8-fold (for Ap9) higher than those of the wild-type strain.…”
Section: Resultsmentioning
confidence: 99%
“…[ 1 ] The SARS‐CoV‐2 pandemic has resulted in an increased usage of all antibiotics, further exacerbating the risks of bacterial resistance. [ 2 ] Therefore, in recent years, the crisis of multidrug‐resistant bacteria caused by antibiotic resistance has plagued human health and animal husbandry. [ 3 ] In addition, the Chinese government has issued the policy to ban the addition of feed antibiotics in feed and breeding from July 1, 2020, which has led to a significant increase in the demand for antibiotic substitutes in feed.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial peptides are molecules made up of amino acids produced by the body, they are an important part of the body's immune system (Vimberg et al, 2022). Peptides have low molecular weight, broad antibacterial spectrum, and endurance to resistance (Lin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%